Perinatal outcome in gestational hypertension: Which role for developing preeclampsia. A population-based cohort study. (August 2020) - Moresi, Sascia; Martino, Carmelinda; Salvi, Silvia; Del Sordo, Gelsomina; Fruci, Stefano; Garofalo, Serafina; Lanzone, Antonio; De Carolis, Sara; Ferrazzani, Sergio
Highlights: Pregnancy outcome in gestational hypertension is less favorable than expected. Risk of having either iatrogenic or spontaneous preterm birth is double. Risk of developing preeclampsia is 62 % when the diagnosis is earlier than 28 weeks. In pharmacologically treated women, the rate of preeclampsia is 5 times higher. Small infants' rate is similar between who develop and not develop preeclampsia. Abstract: Objective: To analyze perinatal outcome in singleton pregnancies complicated by gestational hypertension (GH), to investigate the rate of women developing preeclampsia (PE) and to describe maternal features associated with progression to PE. Study design: This is a population-based retrospective cohort-study involving 514 singleton pregnancies with a diagnosis of GH at admission. Results: In pregnancies with GH, a poorer pregnancy outcome in comparison to healthy controls was observed in terms of gestational age at delivery, birthweight and birthweight percentile. The observed overall rate of developing PE was 11.7 %. Of all pregnancies with GH at admission, two different groups were identified based on the diagnosis at delivery: GHPE, i.e. women who developed PE (60/514; 11.7 %), and GHnoPE, i.e. women who did not develop PE (454/514; 88.3 %). In the GHPE group it was observed that the 62 % of the women with diagnosis of GH earlier than 28 weeks developed PE while only 2% developed PE if the diagnosis of GH was performed later than 36 weeks. The observed rate of developing PE was 14.7 % in pharmacologically treated hypertensive women, whereas the diagnosis of PE has been made in only 3% of non-treated women. Conclusion: Pregnant women with raised blood pressure are at risk of having a less favourable perinatal outcome. The risk is mainly associated with the progression to PE. Major determinants of the risk of developing PE are the earlier gestational age at diagnosis of GH, the necessity of treatment and the number of anti-hypertensive drugs needed for controlling blood pressure.